"The Whole Peace Corps Thing" : a Rhetorical Analysis of Peace Corps Volunteer Blogs - Gannon, Danielle (My University, 2010)
This rhetorical analysis will explore the narratives of Peace Corps Volunteers as expressed through blog entries on www.peacecorpsjournal.gov. This specific research will add to the understanding of how individual, organizational and cultural narratives interact and are manifested in language.
Color poster with text and images.
Keywords: Peace Corps (U.S.)--Blogs; Peace Corps (U.S.)--Personal narratives; Volunteers--Blogs; Volunteers--Personal narratives; Volunteers--Attitudes; Posters